Analysis of Supply Chain Management System Using Lean Six Sigma with Performance Indicator Measurement Control - Wahyu Eko Prasetyo; Rita Ambarwati (Telaah Bisnis, 2022)
The potential for the development of the beauty product industry in Indonesia is considered very potential. The beauty product industry and trade in Indonesia is projected to increase by USD 7.5 billion with a growth of 6.5% annually for the next five years. The huge potential in the cosmetic retail business is considered to trigger competition, especially in the supply chain system which has implications for product affordability to consumers. So that this becomes an interesting condition for research as well as efforts to provide certain improvement treatments so that there is an improvement in the supply system flow in the object company. In this study, 3 layers of the research process will be carried out, namely observing and describing the existing supply chain system in the research object company, supply chain system improvement and treatment using the lean six sigma model with the stages define, measure, analyze, improve, control (DMAIC), and make observations as well as measurement of improvement results using 4 (four) balanced score card performance indicators. Excavation of data using the method of observation, interviews, scoring key performance indicators in each perspective, and study of the company's operational administration data. Based on the results of the research, the supply system based on 4 balanced-scored card indicators still has shortcomings, namely the debt to equity ratio, customer quantity and quality, internal business organization and personnel accountability. The recommendations of this study can have an improvement effect for object companies and also a reference for other companies specifically with the same segmentation.